Improved dissolution, flow property and compressibility of poor soluble API by co-grinding with fine silica - Chatterjee, Bappaditya (2017)
Objective:The objective of this work was to enhance dissolution and tableting property of a poor soluble API which also has poor flow property. If flowability and compressibility of the API can be improved, the drug powder would be suitable to direct compression method of tableting. Methods:Ibuprofen is chosen as a model poor soluble and poor flowable API. Ibuprofen is mixed with 1 wt% of hydrophobic and hydrophilic silica (particle size < 40 nm) separately by a ‘V’ blender. The mixture was then subjected to milling by a simple lab scale ball mil. The co-milled ibuprofen-silica mixture is then formulated as tablet using 30, 50 and 70% drug loading. Before tableting flow property and bulk density of all the tableting mixtures containing co-milled ibuprofen as well as blended ibuprofen (before milling) along with other inactive excipients were studied by various approaches such as angle of repose (AOR), Carr index (CI) and powder flow tester. The tablets are tested for physico-chemical characteristics and in-vitro dissolution. Results:Tableting mixture of 30% and 50% drug (co milled mixture with hydrophobic silica) loading showed ‘excellent’ flow property by AOR (<30̊), CI (<10) and flow function co-efficient (ffc) (<12). However 70% drug loaded mixture showed ‘poor’ flowability by AOR and CI but comparable flowability by ffc. The compressibility result was superior in 50% co-milled ibuprofen loaded tableting mixture than other mixtures. The simple blended ibuprofen tableting mixture also showed acceptable flowability for 30% and 50% drug loaded mixture. Hydrophilic silica mixed ibuprofen in all cases resulted in ‘fair’ flowability but poor compressibility. Out of the entire tablets 50% co-milled drug loaded tablet showed better dissolution profile by releasing more than 90% of drug within 1 hour which is significantly higher than normal blended ibuprofen loaded tablet. However 70% drug loaded tablet resulted in slow drug release (<59.34% in 1 hour). Conclusion:Co-milling of silica-ibuprofen might be a good strategy to improve flowability and dissolution of the drug. This approach may help preparing tablet by direct compression using high dose poor flowable drug.